Seismic Performance Evaluation of Modern Bare and Masonry-Infilled RC SMRF Structures - M. E. Ahmad; N. Ahmad; S. Pervez; A. Iqbal; A. Z. Khan; M. E. Rahim; W. Hassan; K. Umer; K. Khan (Advances in Civil Engineering)
Improper execution of modern code-designed structures in many developing countries have resulted in significant deficient building stock; low strength of concrete, reduced reinforcement, inappropriate detailing of beam-column members, and lack of lateral ties in joint panels. Observations based on earthquake-induced damages and experimental studies conducted on such buildings have revealed significant vulnerability of beam-column joints of bare moment-resisting frame structures. Shake table tests were conducted on selected three 1 : 4 reduced-scale three-story reinforced concrete (RC) moment-resisting frames, including one bare RC frame and two masonry-infilled RC frames, having relatively lower bay width-to-height ratio. The models were tested under multilevels of seismic excitations using natural acceleration time history of 1994 Northridge and also free vibration tests, to acquire the models’ dynamic characteristics, i.e., frequencies and elastic viscous damping, and seismic response parameters, i.e., roof displacement, interstory drift and interstory shear, and seismic response curves, in order to understand the role of masonry infill in the selected frames under moderate seismic actions. The inclusion of masonry infill avoided joint shear hinging of the frame. Additionally, the infill provided energy dissipation to the structure through masonry sliding over multiple cracks. This enabled the structure to control seismic displacement demand and resist relatively higher ground motions, yet limiting structural damages.